Flibanserin: A Novel, Nonhormonal Agent for the Treatment of Hypoactive Sexual Desire Disorder in Premenopausal Women. (April 2017) - Vallejos, Ximena; Wu, Christine
Objective: To review pivotal clinical trials, pharmacology, contraindications, precautions, and key patient education points of flibanserin for the treatment of hypoactive sexual desire disorder (HSDD) in premenopausal women. Data Sources: A literature search of PubMed using the key words flibanserin and HSDD was conducted in September 2015. There was no time frame to exclude relevant clinical trials. All trials referenced were published between March 2012 and June 2014. Other relevant information was obtained from the Food and Drug Administration (FDA) Web site, press releases, prescribing information from the manufacturer, andClinicalTrials.gov . Study Selection/Data Extraction: All articles in the English language and involving human subjects were reviewed. Data Synthesis: There are three 24-week, multicenter, randomized, double-blind, placebo-controlled trials that evaluated the efficacy of flibanserin in North American premenopausal women with HSDD. There was 1 trial that studied the effects of flibanserin in postmenopausal women. In all of the trials, the investigators found statistical significant improvements in Female Sexual Function Index (FSFI) desire domain score and satisfying sexual events (SSEs). The most frequently reported adverse events in all flibanserin arms of treatment were somnolence, dizziness, and nausea. Conclusion: Flibanserin, a novel, nonhormonal agent that modulates excitatory and inhibitory neurotransmitters was studied in premenopausal women and has shown efficacy in improving sexual desire and SSEs.